Exclusive Territories and Manufacturers' Collusion - Piccolo, Salvatore; Reisinger, Markus (Management Science, 2011)
This paper highlights the rationale for exclusive territories in a model of repeated interaction between competing supply chains. We show that with observable contracts exclusive territories have two countervailing effects on manufacturers' incentives to sustain tacit collusion. First, granting local monopolies to retailers softens competition in a one-shot game. Hence, punishment profits are larger, thereby rendering deviation more profitable. Second, exclusive territories stifle deviation profits because retailers of competing brands adjust their prices to the wholesale contract offered by a deviant manufacturer, whereas intrabrand competition prevents such “instantaneous reaction.” We show that the latter effect tends to dominate, thereby making exclusive territories a more suitable organizational mode to cooperate. These insights are robust to endogenous communication between manufacturers. We also consider retailers' service investments. Here, a novel effect emerges that softens the procollusive value of exclusive territories: Retailers of a deviant manufacturer increase investments, which renders deviation more profitable. This paper was accepted by Preyas Desai, marketing.